Journal of developing societies JDS. (SAGE, 2002)
The Journal of Developing Societies is a refereed international journal on development and social change not only in 'developing' countries but also the 'developed' societies of the world. It provides an interdisciplinary forum for the publication of theoretical perspectives, research findings, case studies, policy analyses and normative critiques on the issues, problems and policies of both mainstream and alternative approaches to development. The journal represents the full range of diverse theoretical and ideological viewpoints on development that exist in the contemporary international community.